Magnesium sulfate for fetal neuroprotection in preterm pregnancy: a meta-analysis of randomized controlled trials - Kyana Jafarabady; Arman Shafiee; Nasim Eshraghi; Seyyed Amirhossein Salehi; Ida Mohammadi; Shahryar Rajai; Zahra Zareian; Fatemeh Movahed; Mahmood Bakhtiyari (BMC, 2024)
Abstract Background Intravenous administration of magnesium sulfate (MgSO4) to expectant individuals before childbirth, has been evaluated to reduce the likelihood of mortality and occurrence cerebral palsy in their offspring. Therefore, this systematic review and meta-analysis conducted to determine if were the prophylactic use of magnesium sulfate in women at risk for preterm delivery leads to decrease in the incidence of death or cerebral palsy. Methods A comprehensive search of electronic databases was done to identify relevant studies. Selection of eligible studies was based on predetermined inclusion criteria. Data extraction was performed, and the methodological quality of the selected studies was assessed using appropriate evaluative tools. A meta-analysis was carried out to estimate the overall effect of intravenous administration of magnesium sulfate on the incidence of death or cerebral palsy. Results A total of 7 studies met the inclusion criteria and were included in the final analysis. No significant publication bias was observed. The risk of fetal neurological impairment was significantly lower in the MgSO4 group compared to the control group relative risk (RR = 0.70, 95% CI: 0.56 to 0.87; I20%). However, neonatal mortality was not significantly associated with MgSO4 injection. (RR = 1.03, 95% CI: 0.88 to 1.21; I2 = 42%). Subgroup analysis was done based on the bolus dosage of MgSO4 and the duration of the trial follow-up. revealing a non-significant differences between-group. Conclusion This study demonstrated that MgSO4 administration can improve fetal neurological impairment and cerebral palsy but is not linked to reducing mortality. Further studies are necessary to strengthen the evidence and clarify the underlying mechanisms.